An exploratory study of crowding during mass celebrations in Quiapo church - Libutan, Dennilie Ivy D.; Quevedo Ma. Teresa P. (Quezon City UP College of Home Economics, 2011)
This exploratory study aimed to investigate whether crowding was present during mass celebrations in Quiapo Church by examining the physical conditions inside the church evaluating the over-all experience of selected churchgoers during mass celebrations. The study utilized both qualitative and quantitative approaches and employed survey and observation. Among the tools used were survey questionnaires and observation checklist. One hundred nineteen churchgoers of Quiapo Church served as respondents for the study and were chosen through random convenience sampling. Results revealed that crowding in the physical state was evident as seen in the large number of churchgoers who could not be accommodated by the number of pews inside the church. Crowding was also experienced by the respondents as manifested through stimulus overload, behavioural constraint, impaired task performance, and density - intensity hypothesis. Among these indicators, stimulus overload and behavioral constraint were the most evident. Consequently, crowding produced negative effects on the respondents. These negative effects were disturbance, anxiousness, dissatisfaction in conducting church activities, lost of focus during mass, and withdrawal or leaving before the mass ends. To cope with crowding, the respondents developed coping mechanisms, the most significant of which are those addressing stimulus overload such as sitting or standing near the window or electric fan, bringing fans, and wearing comfortable clothes. In conclusion, the Quiapo Church did not succeed in providing a suitable environment for mass celebrations and thus failed to function according to its purpose. Despite this, large number of devotees can be seen coming to Quiapo Church everyday. The importance given by the Filipino Churchgoers to their religious belief is such that even though the church did not provide an environment that was fit for mass celebrations, they still go to Quiapo Church and hear mass.
Thesis (BSID)--University of the Philippines Diliman.
Keywords: Catholic church buildings -- Philippines -- Design and construction; Quiapo church